A Wild Sheep Chase - Murakami, Haruki (Random House - Vintage Books Londýn, 2003)
A marvelous hybrid of mythology and mystery, A Wild Sheep Chase is the extraordinary literary thriller that launched Haruki Murakami's international reputation.
It begins simply enough: A twenty-something advertising executive receives a postcard from a friend, and casually appropriates the image for an insurance company's advertisement. What he doesn't realise is that included in the pastoral scene is a mutant sheep with a star on its back, and in using this photo he has unwittingly captured the attention of a man in black who offers a menacing ultimatum: find the sheep or face dire consequences. Thus begins a surreal and elaborate quest that takes our hero from the urban haunts of Tokyo to the remote and snowy mountains of northern Japan, where he confronts not only the mythological sheep, but the confines of tradition and the demons deep within himself. Quirky and utterly captivating, A Wild Sheep Chase is Murakami at his astounding best.
Dvadsaťročný manažér reklamy dostane pohľadnicu od priateľa a neformálne si obrázok privlastní pre reklamu poisťovacej spoločnosti. Neuvedomuje si, že na pastierskej scéne je zmutovaná ovca s hviezdou na chrbte a pri použití tejto fotografie nechtiac upútal pozornosť muža v čiernom, ktorý ponúka hrozivé ultimátum: nájsť ovcu alebo čeliť hrozným následkom. Začína sa tak surrealistické a prepracované pátranie, ktoré zavedie nášho hrdinu z mestských strašidiel v Tokiu do odľahlých a zasnežených hôr severného Japonska, kde čelí nielen mytologickým ovciam, ale aj hraniciam tradície a démonov hlboko v sebe.
Keywords: japonská literatúra; spoločenské romány; fantastické romány; triler; texty v angličtine